The Relationship between Tuberculosis and Corona Virus - Shareef, Saja A.; Aldulaimy, Mays K.; Mohammed, Walaa A. (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
In 2020, COVID-19 and tuberculosis emerged as significant threats to global health, with increased mortality and decreased testing due to the pandemic's impact on the tuberculosis care system. Both diseases spread through respiratory system secretions and airborne particles, with the lungs being their primary target organ. Common remedies include addressing the spread of Mycobacterium tuberculosis and addressing the underlying causes of both diseases. COVID-19 diagnostics include quick antigen test kits and RT-PCR, while tuberculosis diagnostics include chest X-rays, sputum microscopy, and RT-PCR on sputum. These methods allow for same-day active TB diagnosis, compared to culture-based testing that could take up to eight weeks. Using a range of diagnostic tools ensures that COVID-19 and TB patients are identified and treated promptly. The combined danger of TB and COVID-19 presents a significant challenge to patient quality of life. To effectively combat this combined threat, cooperation, research funding, and policy changes are necessary.